Pengaruh Brand Awareness, Brand Loyalty Dan Brand Image Terhadap Keputusan Pembelian Produk The Originote (Studi Kasus Pada Generasi Muda Di Kec. Lowokwaru Kota Malang) - Wati, Bela Sinta; Maslichah, Maslichah; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study intends to examine the factors that have an impact on the purchase decision of The Originote products in Lowokwaru District, Malang City, with a focus on consumers from the younger generation. The research approach applied is quantitative with a correlational method. Sampling was carried out using a purposive sampling technique with a total of 90 respondents. Based on the results of multiple linear regression analysis, it was found that Brand Awareness and Brand Loyalty have a positive and significant impact on purchase decisions. In contrast, Brand Image shows a significant negative impact on purchasing decisions. This output confirms that increasing brand awareness and customer loyalty are able to increase the tendency of users to shop for The Originote products. However, a poor brand image can hinder the purchase decision-making process. This research highlights the importance of the right marketing scheme for increasing brand awareness and customer loyalty. Companies need to implement more transparent communication and build consumer trust to strengthen a positive brand image. The results of this research can be used as a reference for marketers and academics in designing marketing strategies in the increasingly competitive cosmetics industry. Keywords: Brand Awareness, Brand Loyalty, Brand Image.